1991
DOI: 10.1111/j.1365-2125.1991.tb05619.x
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with conventional and controlled‐release carbamazepine: a double‐blind, double‐dummy comparison in epileptic patients.

Abstract: 1 Twenty-one epileptic patients completed a double-blind, double-dummy, random order, crossover comparison of conventional carbamazepine (CBZ, Tegretol, CibaGeigy) with a new controlled-release formulation (CBZ-CR, Tegretol Retard). All participants were stabilised on maximally tolerated doses of CBZ as monotherapy (one twice daily, twelve three times daily, eight four times daily). Each preparation was taken with a matched placebo of the other for 4 weeks. 2 Peak serum CBZ concentrations (mean ± s.e. mean) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A MR dosage formulation is one that has been pharmaceutically engineered to be delayedrelease (a tablet coating that prevents drug release initially, then some time later releasing all drug immediately), or extended-release (ER), or manufactured to exhibit some combination of active drug ingredient release rates over time in the gastrointestinal tract. Each MR AED [CBZ (18)(19)(20)(21)(22)(23)(24)(25); PHT (26); divalproex ⁄ VPA (27)(28)(29)(30)(31)(32)(33)(34)(35)(36); LTG (15,(37)(38)(39)(40); LEV (41,42)] is formulated with the intent of achieving improved seizure control in patients with epilepsy (1,(43)(44)(45)(46)(47)(48)(49), via minimization of peak-trough plasma AED concentration fluctuation, thus reducing peak AED-concentration-related adverse events, increasing convenience for the patient by permitting a reduction in the dosing frequency or interval and hopefully augmenting adherence.…”
Section: Resultsmentioning
confidence: 99%
“…A MR dosage formulation is one that has been pharmaceutically engineered to be delayedrelease (a tablet coating that prevents drug release initially, then some time later releasing all drug immediately), or extended-release (ER), or manufactured to exhibit some combination of active drug ingredient release rates over time in the gastrointestinal tract. Each MR AED [CBZ (18)(19)(20)(21)(22)(23)(24)(25); PHT (26); divalproex ⁄ VPA (27)(28)(29)(30)(31)(32)(33)(34)(35)(36); LTG (15,(37)(38)(39)(40); LEV (41,42)] is formulated with the intent of achieving improved seizure control in patients with epilepsy (1,(43)(44)(45)(46)(47)(48)(49), via minimization of peak-trough plasma AED concentration fluctuation, thus reducing peak AED-concentration-related adverse events, increasing convenience for the patient by permitting a reduction in the dosing frequency or interval and hopefully augmenting adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study also described the lower diurnal fluctuation obtained with Tegretol Retard' in 21 patients with epilepsy This study concludes that 'Tegretol Retard' is a pharmacokinetically attractive method of administering carbamazepine and produces fewer sUbjective side effects. However, 'Tegretol Retard' resulted in lower mean carbamazepine concentrations when given in the same total daily dose as the conventional preparation ('Tegretol') and may be less effective unless the dose is modified (McKee et al 1990(McKee et al , 1991. During a 3-month double-blind crossover study (Persson et al 1990), a slow release formulation of carbamazepine ('Neurotol Slow') was found to produce fewer side effects than a conventional preparation ('Neurotol'), while an earlier study showed that there appeared to be a correlation between the frequency of side effects associated with carbamazepine treatment and the daily variations in peak serum concentrations (Tomson 1984).…”
Section: Carbamazepinementioning
confidence: 93%
“…This reduced the fluctuation in concentration during a dosage interval by around 50% in healthy volunteers [3]. In epileptic patients, less diurnal fluctuation in serum drug concentrations and minor improvements in psychomotor function were found with twice daily CBZ-MR compared with three and four daily dosing with conventional CBZ [4].…”
Section: Introductionmentioning
confidence: 94%
“…The patient may realise these kinetic benefits in fewer side-effects, improved compliance and better seizure control [2,22]. Open [18,23,24], singleblind [19,25] and double-blind studies in healthy volunteers and in epileptic patients [3,4,17,20,21,26] have shown that twice daily administration of CBZ-MR has a pharmacokinetic profile and efficacy similar to three and four times daily dosing with conventional CBZ. Formal psychomotor testing using adequate placebo controls also favoured CBZ-MR [4,25].…”
Section: Discussionmentioning
confidence: 99%